2019
DOI: 10.1111/bph.14873
|View full text |Cite|
|
Sign up to set email alerts
|

Costunolide represses hepatic fibrosis through WW domain‐containing protein 2‐mediated Notch3 degradation

Abstract: Background and Purpose This study investigates the antifibrotic activities and potential mechanisms of costunolide (COS), a natural sesquiterpene compound. Experimental Approach Rats subjected to bile duct ligation and mice challenged with CCl4 were used to study the antifibrotic effects of COS in vivo. Mouse primary hepatic stellate cells (pHSCs) and human HSC line LX‐2 also served as an in vitro liver fibrosis models. The expression of fibrogenic genes and signaling proteins in the neurogenic locus notch hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 41 publications
0
24
1
Order By: Relevance
“…Studies also show that CTD inhibits the differentiation and represses hepatic fibrosis by regulating mitogen-activated protein kinases and Notch3 degradation, respectively. Or it suppresses the colon cancer growth by the Wnt/β-Catenin pathway [ 34 36 ]. However, our findings suggest that CTD regulates MDM2/p53 interaction by inhibiting AKT activation, which thereby increase apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that CTD inhibits the differentiation and represses hepatic fibrosis by regulating mitogen-activated protein kinases and Notch3 degradation, respectively. Or it suppresses the colon cancer growth by the Wnt/β-Catenin pathway [ 34 36 ]. However, our findings suggest that CTD regulates MDM2/p53 interaction by inhibiting AKT activation, which thereby increase apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Costunolide possesses anti-angiogenic [9,10] and -osteoarthritic effects [11]. It inhibits pulmonary [12] and hepatic fibrosis [13], induces hair growth [14] and shows strong larvicidal activity [15]. Furthermore, costunolide induces apoptosis, an evolutionary conserved cellular programmed cell death by conjugating with sulfhydryl groups and intracellular thiols, e.g.…”
mentioning
confidence: 99%
“…Splicing is expected to be a major source of untapped molecular targets for precision oncology [ 33 ]. PPM1G plays a fundamental role in increasing liver fibrosis by negatively regulating the effect of WWP2 on Notch3 degradation [ 4 ]. More than 80% of hepatocellular carcinoma tumors develop in fibrotic or cirrhotic livers, suggesting an important role of liver fibrosis in the premalignant environment of the liver [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological research has shown that more than 80% of hepatocellular carcinomas develop in fibrotic or cirrhotic livers [ 3 ]. PPM1G plays a fundamental role in increasing liver fibrosis by negatively regulating the effect of WWP2 on Notch3 degradation [ 4 ]. The inhibition of PPM1G activity by CdCl2 also decreases the protein levels of fibrogenic markers [ 5 ].…”
Section: Introductionmentioning
confidence: 99%